Positional Accuracy Evaluation of Google Earth using RTK GNSS Network Surveying Case Study: Mahasarakham Province - Srihanu, Neti; Kaewplang, Siwa (Journal of Applied Informatics and Technology, 2021)
This study aims to provide an understanding of the horizontal positional accuracy and Google Earth height compare with Static GNSS surveying. The results showed the RMSE obtained in E, N, Z(EGM96), and Z (TGM2017) were 1.316, 1.331, 3.558, and 4.453 m. respectively with a horizontal error range of -2.834 m to 1.930 m and a vertical error range of -0.673 m to 8.874 m in all 48 measured points. The results show Google Earth cannot provide high accuracy coordinate and the height of google earth is not so sensitive to immediate changes in ground topography.